A novel approach for large-scale manufacturing of small extracellular vesicles from bone marrow-derived mesenchymal stromal cells using a hollow fiber bioreactor - Jakl, Viktoria; Ehmele, Melanie; Winkelmann, Martina; Ehrenberg, Simon; Eiseler, Tim; Friemert, Benedikt; Rojewski, Markus Thomas; Schrezenmeier, Hubert (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stromal cells (MSC) are promising therapeutic candidates in a variety of diseases by having immunomodulatory and pro-regenerative properties. In recent years, MSC-derived small extracellular vesicles (sEV) are attracting increasing interest as a possible alternative to conventional cell therapy. However, translational processes of sEV for clinical applications are still impeded by inconsistencies regarding isolation procedures and culture conditions. We systematically compared different methods for sEV isolation from conditioned media of ex vivo expanded bone marrow-derived MSC and demonstrated considerable variability of quantity, purity and characteristics of sEV preparations obtained by these methods. The combination of cross flow filtration with ultracentrifugation for sEV isolation resulted in sEV with similar properties as compared to isolation by differential centrifugation combined with ultracentrifugation, the latter still considered as gold standard for sEV isolation. In contrast, sEV isolation by a combination of precipitation with polyethylene glycol and ultracentrifugation as well as cross flow filtration and size exclusion chromatography resulted in sEV with different characteristics as shown by surface antigen expression patterns. The MSC culture requires a growth-promoting supplement, like e.g., platelet lysate which contains sEV itself. We demonstrated that MSC culture with EV-depleted platelet lysate does not alter MSC characteristics and conditioned media of such MSC cultures provides sEV preparations enriched for MSC-derived sEV. In conclusion, combining our data from the systematic stepwise evaluation of various aspects with culture of MSC in a hollow fiber bioreactor demonstrates that this workflow - using cross flow filtration with subsequent ultracentrifugation for sEV isolation - provides a semi-automated, efficient, large-scale-applicable and good manufacturing practice (GMP)-grade approach for generation of sEV for clinical use. The use of EV-depleted platelet lysate is an option to further increase the purity of MSC-derived sEV.